2014
DOI: 10.2337/db13-1455
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of GLP-1 in the Enteroinsulinar Axis in Type 2 Diabetes Using DPP-4 Inhibition and GLP-1 Receptor Blockade

Abstract: Understanding the incretin pathway has led to significant advancements in the treatment of type 2 diabetes (T2D). Still, the exact mechanisms are not fully understood. In a randomized, placebocontrolled, four-period, crossover study in 24 patients with T2D, dipeptidyl peptidase-4 (DPP-4) inhibition and its glucose-lowering actions were tested after an oral glucose tolerance test (OGTT). The contribution of GLP-1 was examined by infusion of the GLP-1 receptor (GLP-1r) antagonist exendin-9. DPP-4 inhibition redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 50 publications
10
72
0
Order By: Relevance
“…This might relate to the effects of peptide YY (PYY), whose degradation from PYY1-36 to PYY3-36, which has more potent effects to slow gastric emptying, is prevented by DPP-4 inhibition (50). The current data are thus in keeping with the majority of evidence that DPP-4 inhibition does not influence gastric emptying (17)(18)(19)21,22), although a recent study reported slowing of oral glucose emptying after sitagliptin in type 2 diabetic patients (20). Metformin was reported to slow gastric emptying in mice (25), but we did not observe any effect on APD motility in the current experimental setting.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This might relate to the effects of peptide YY (PYY), whose degradation from PYY1-36 to PYY3-36, which has more potent effects to slow gastric emptying, is prevented by DPP-4 inhibition (50). The current data are thus in keeping with the majority of evidence that DPP-4 inhibition does not influence gastric emptying (17)(18)(19)21,22), although a recent study reported slowing of oral glucose emptying after sitagliptin in type 2 diabetic patients (20). Metformin was reported to slow gastric emptying in mice (25), but we did not observe any effect on APD motility in the current experimental setting.…”
Section: Discussionsupporting
confidence: 75%
“…The lack of glucose lowering with sitagliptin in type 2 diabetic subjects, therefore, supports the hypothesis of a defective glucoregulatory capacity of endogenous GIP in this group and is consistent with the marked impairment of glucose lowering by sitagliptin in type 2 diabetic patients after oral glucose during GLP-1 antagonism with exendin-(9-39) (20). Although insulin response to exogenous GIP can be partly restored with strict glycemic control in type 2 diabetes, its insulinotropic effect is not associated with improvement in glucose disposal during hyperglycemic clamp studies (41).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Indeed, several biological peptides apart from the GLP-1 are potentially substrates for DPP-4 although most of these findings are not relevant in vivo (4). Indirect evidence that other peptides than GLP-1 may contribute to the effects of DPP-4 inhibition was recently presented by Aulinger et al (38). They showed that the GLP-1 receptor antagonist exendin-9 could inhibit the effect of sitagliptin on glucose and insulin secretion by only ;50% after 4 weeks of treatment with the DPP-4 inhibitor in type 2 diabetes.…”
Section: Prevention Of Inactivation Of Other Biologically Active Peptmentioning
confidence: 98%
“…In patients with type 2 diabetes, insulinogenic indices (based on insulin, C-peptide, or insulin secretory rates) were increased by vildagliptin and reduced by exendin , but, importantly, the difference between these conditions was only ;50%. Hence, as concluded by Aulinger et al (10) who evaluated the effects of sitagliptin, only about half of the insulinotropic effect of DPP-4 inhibition could be attributed to GLP-1. Exendin also accelerated gastric emptying, whereas vildagliptin apparently had no effect.…”
Section: Dpp-4 Inhibition and The Known Unknownmentioning
confidence: 78%